Prevalence of obligate anaerobes and aerobes in uterine lumen of subfertile crossbred cows in relation to physical appearance of cervicovaginal mucus - DHILLON, N S; DHALIWAL, G S; DADARWAL, D; ARORA, A K; KAUR, PAVITER (The Indian Journal of Animal Reproduction, 2023)
Aerobes causing bacterial endometritis have been investigated under Indian condition but involvement of obligate anaerobes have not been studied so far. In the present study, 30 subfertile pleuriparous crossbred cows with the history of not conceiving within 5-18 months of calving and had received 3 AI with fertile semen and lacked genital abnormalities; were selected from the university dairy farm. These cows were gred on the basis of colour of cervico-vaginal mucus viz .. gr I ( clear mucus, n=I 2). gr 2 (muco-purulent, n=I 0) and gr 3 (purulent mucus n=8). The uterine swabs taken during estrus with the help of guarded Neilson ’s Swab Catheter, were subjected to bacteriological culture for isolation of obligate anaerobes and aerobes. Out of total 42 bacterial isolates recovered 16 were obligate anaerobes while 26 were aerobes. Two cows harbored only obligate anaerobes, l O cows only aerobes, 13 cows both obligate anaerobes and aerobes and the remaining 5 cows were bacteriologically sterile. Amongst the gram negative anaerobes (GNA), Bacteroides sp. predominated in all the three grs. Amongst aerobes, E. coli and/or Pseudomonas sp. predominated in Grs l and 2 and Arcanobacter pyogenes in gr 3. Cows of gr 3 showed the highest prevalence of mixed infection of both GNA and aerobes. Amongst the mixed infections, combination of Bacteroides anaerobes with£. coli and/or Pseudomonas predominated in gr I and 2 while that of Bacteroides sp with Arcanobacler pyogenes in gr 3. Out of total 26 aerobic isolates, 7 were of Arcanobacter pyogenes, of which 5 grew in combination with GNA and 2 were in pure growth. To conclude, nearly half of bacteria positive subfertile cross-bred cows had mixed infection of obligate anaerobes and aerobes. Cows with clear and/or mucopurulent discharge harbored mainly GNA occurring in combination with E. coli I Pseudomonas sp while those with purulent mucus had gram negative obligate anaerobes coupled with Arcanobacter pyogene.